2018
DOI: 10.1111/dar.12697
|View full text |Cite
|
Sign up to set email alerts
|

What is going on in underage drinking? Reflections on Finnish European school survey project on alcohol and other drugs data 1999–2015

Abstract: Formal policy measures and adults' attitudes have probably affected the availability of alcohol for adolescents, and thus they partly explain the decline in youth drinking. This decline coincides with the introduction of new digital technologies, new forms of interaction within families and peer groups, and more conscientious teenagers. All these changes are not necessarily causes of the decline but are part of a similar broader change in adolescents' lives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
49
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 30 publications
9
49
0
1
Order By: Relevance
“…Our results support findings in other studies, suggesting changes in the normative climate around drinking among young people, increased emphasis on academic achievement and a disciplined way of life, and a more health-oriented lifestyle as explanations for non-drinking [1,[7][8][9][10]. They also align with Kraus et al [10] who hypothesise that changes in the social position of alcohol are related to how its perceived negative effects do not fit with an increasingly healthoriented youth culture, and also to changes in technology, social norms and family relationships.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results support findings in other studies, suggesting changes in the normative climate around drinking among young people, increased emphasis on academic achievement and a disciplined way of life, and a more health-oriented lifestyle as explanations for non-drinking [1,[7][8][9][10]. They also align with Kraus et al [10] who hypothesise that changes in the social position of alcohol are related to how its perceived negative effects do not fit with an increasingly healthoriented youth culture, and also to changes in technology, social norms and family relationships.…”
Section: Discussionsupporting
confidence: 88%
“…Scholars have offered a number of possible explanations for the declining trend in alcohol use among younger adolescents. These include: better enforcement of the minimum legal age for alcohol purchase; changes in social norms related to drinking among young people and immigration from non-drinking cultures; a more competitive society with an emphasis on academic achievement and a disciplined way of life; a more health-oriented lifestyle; changes in parenting and parental norms; lower affordability and the rise of internet-based technologies [1,[7][8][9][10]. There are still rather few empirical studies assessing whether, or to what extent, one or more of these explanations are valid [1,9,11].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies indicate that increased parental knowledge and stricter alcohol-specific parenting have contributed to the downward drinking trend [6,[11][12][13]. Kraus et al [7] suggested that parents have also become less likely to drink in front of their adolescent children.…”
Section: Discussionmentioning
confidence: 99%
“…The changes in youth drinking seem to have been concurrent with changes in parenting practices; six studies in this special issue identify increases in parental supervision [6][7][8][9][10][11] and parents' attitudes towards youth drinking becoming more restrictive [6,7,9,11]. Larm et al [6], however, also show changes in parenting practices of the same magnitude among those youth that drink, which implies a general increase in parental supervision that is not confined to non-drinking youth.…”
mentioning
confidence: 98%
“…The changes in youth drinking seem to have been concurrent with changes in parenting practices; six studies in this special issue identify increases in parental supervision and parents’ attitudes towards youth drinking becoming more restrictive . Larm et al .…”
mentioning
confidence: 99%